Sustainable Supply Chain Management Integration: A Qualitative Analysis of the German Manufacturing Industry - Wolf, Julia (2011)
Firms are increasingly integrating sustainability into their supply chain management (SCM) practices. The goal is to achieve sustainable flows of products, services, information and capital to provide maximum value to all corporate stakeholders. Prior research on SCM integration has insufficiently addressed sustainability. The objective of this research is to provide for a coherent and testable model of sustainable supply chain management integration (SSCMI). By drawing on four cases from the German manufacturing industry, we seek to identify the most important factors that enable or impede the integration of sustainability into SCM.
Keywords: case study research; Conceptual Framework; Sustainability; Supply Chain Management; Integration